Pendampingan Penyusunan RPS Berbasis OBE sebagai Strategi Peningkatan Capaian IKU PT - Desi Indriyani; Nuris Hidayat; Famela Ainina Susanti Wijaya; Mohammad Dodik Efendi (GUNAVATTA : Jurnal Pengabdian Masyarakat, 2025)
The quality of higher education is strongly influenced by lecturers' ability to design learning that is relevant, adaptive, and outcome-oriented. One strategic effort to improve learning quality is through the development of a Semester Learning Plan (RPS) based on Outcome-Based Education (OBE), which supports the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy and the achievement of Key Performance Indicators for Higher Education (IKU PT), particularly IKU 7, collaborative and participatory classes. This community service activity was carried out in the form of a workshop on OBE-based RPS preparation for all lecturers at Universitas Abdurachman Saleh Situbondo. The method included delivering OBE concepts, assisting in the preparation of RPS using Problem-Based Learning (PBL) and Project-Based Learning (PjBL) methods, and aligning assessment components according to the IKU guidelines. The results showed increased lecturer understanding of OBE and its application in RPS, as well as a significant contribution to the achievement of IKU PT number 7, reaching a score of 30.82 in 2024 with a growth rate of 28.59 from the 2023 achievement. Other impacts included a more interactive and contextual learning environment for students and improved institutional readiness for quality audits and accreditation processes. This activity proved effective as a strategy to enhance lecturers’ pedagogical competence and the overall quality of higher education.